A bipolar macrospirocyclic oligomer based on triphenylamine and 4, 5-diazafluorene as a solution-processable host for blue phosphorescent organic light-emitting diodes. (November 2016) - Li, Nengquan; Fan, Zhaokang; Zhao, Huiru; Quan, Yiwu; Chen, Qingmin; Ye, Shanghui; Li, Shuhua; Fan, Quli; Huang, Wei
Abstract: A bipolar macrospirocyclic trimer based on 4, 5-diazafluorene and triphenylamine was prepared as a host for solution-processed blue phosphorescent organic light emitting diodes. The oligomer exhibits a high triplet energy of 2.88 eV, excellent thermal and morphological stability, good film-forming ability and solution processability. A solution-processed phosphorescent device based on FIrpic and the trimer achieved a maximum current efficiency of 10.0 cd A −1 with a low current efficiency roll-off at the practical luminance (9.6, 10.0, 9.4 cd A −1 at 102, 207, 1096 cd m −2, respectively). The oligomer additionally showed excellent chemical compatibility with the common host for solution-processing technology. A blue phosphorescent device using mixed hosts of the trimer/4, 4′-cyclohexylidenebis( N, N -bis(4-methyl -phenyl)benzenamine) achieved a low turn-on voltage of 3.0 V, a maximum luminance of 28, 368 cd m −2, and a maximum current efficiency of 17.7 cd A −1 (11.9 lm W −1 ), which is almost three times that of a single 4, 4′-cyclohexylidenebis( N, N - bis(4-methylphenyl)benzenamine)-hosted device. Highlights: A bipolar macrospirocyclic oligomer was prepared through a simple reaction. Good doping compatibility, excellent thermal stability and high triplet energy 2.88 eV. Solution processed device exhibits two-fold of improvement in luminous efficiency.